Where does morality come from? Aspects of Nietzsche’s genealogical critique of morality and his idea of the Übermensch - Ku, Hay Lin Helen (2013)
With this dissertation, firstly, I address the issue of Friedrich Nietzsche’s (1844-1900) so-called ‘immoralism’. When he calls himself an ‘immoralist’ and even ‘the first immoralist’ (EH Destiny 2), he seems to be the first philosopher to consider morality as something negative, something we had better got rid of. Yet, he favours ‘noble morality’ and ‘higher moralities’ which he insists ought to be possible (BGE 202). I shall interpret Nietzsche’s explicit claim of ‘immoralism’ and his ‘campaign against morality’ as a rejection of a particular kind of morality ¾ Christian morality ‘that has become prevalent and predominant as morality itself’ (EH Destiny 4). His ‘immoralism’ does not reject the idea of an ethical life. Nietzsche favours a ‘supra-moral’ version of life (GM II 2&BGE 257). The move from a moral to a supra-moral orientation to life implies a kind of self-overcoming, a process which has both a ‘negative’ (‘destructive’) and a ‘positive’ (‘productive’) side. Firstly, I shall give an account of the ‘negative’ side, which involves Nietzsche’s genealogical critique of morality. In his Genealogy, Nietzsche criticizes the man of ressentiment, the metaphysical two-worlds distinction: ‘true world’ and ‘apparent world’, and the ascetic ideal of the will to truth, which he considers as a will to nothingness (GM III 28). His notion of perspectivism advocates a plurality of values and perspectives as opposed to any notion of an absolute truth. Then, I shall look into his ‘positive’ ethic, as exemplified in the figures of Zarathustra and the Übermensch, and the paradox of the Übermenschas ‘the annihilator of morality’ (EH Books 1) and as ‘the designation of a type of supreme achievement’ (EH Books 1). By proclaiming a process of ‘self-overcoming of morality’ (BGE 32), I believe that Nietzsche proposes an experimental morality in order to improve mankind. He considers morality as a pose, as progress (BGE 216), and ‘mere symptomatology’ (TI ‘Improvers’ of Mankind 1). Morality is the effect, or symptom of a continuous improvement within an individual. Nietzsche seeks to make us become aware of our continuous self-improvement, that we should invent our own virtue (A 11) in order to become what we are. Nietzsche envisions the possibility of evolving a magnanimous and courageous human type who is capable of giving style to his character (GS 290), the supreme human achievement ¾ the Übermensch. His idea of the Übermensch implies a never-ending struggle for self-perfection and self-fulfilment. There are affinities between Nietzsche’s philosophy and Buddhism, such as emphasizing practice, the recognition of the transient nature of human existence, and an emphasis on impermanence. Buddhist teachings show various feasible ways to attain enlightenment and buddhahood. The path to enlightenment and buddhahood can be shown to share some features with Nietzsche’s process of self-overcoming, which leads to self-transformation and self-perfection. The emphasis on the practice of the spirit of Bodhisattva by Humanistic Buddhism seems to lend itself as complement to Nietzsche’s philosophy, a notion I explore in the concluding chapter of the dissertation. === Dissertation (MA (Philosophy))--University of Pretoria, 2005. === Philosophy === unrestricted